EKSPLORASI HUBUNGAN HARGA DIRI DAN KONFORMITAS REMAJA DALAM PERGAULAN SEBAYA - Setiyowati , Eny (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Abstract : This study aims to explore the dynamics of the relationship between self-esteem and conformity among adolescents in the context of peer interaction. A qualitative phenomenological approach was employed, involving six adolescent participants aged 15–18 years. Data were collected through in-depth interviews, observations, and documentation, and analyzed using Miles & Huberman’s model, which includes data reduction, data display, and conclusion drawing. The findings reveal that self-esteem plays a crucial role in adolescents’ responses to peer pressure. Adolescents with high self-esteem tend to be more selective and capable of resisting negative conformity, while those with low self-esteem are more likely to yield to peer pressure. Moreover, the study identified positive conformity that supports adaptive behaviors such as group studying. This research contributes theoretically by highlighting self-esteem as a protective factor against negative conformity, and provides practical implications for parents, educators, and counselors in supporting adolescent development. Keywords: self-esteem, conformity, adolescents, peer interaction